The global market impact - Video Education Australasia (Australia : Video Education Australasia, 1998)
This program looks at the impact of global competition and international trade on the Australian economy. It examines how the resulting changes have affected work, employers and employees. Geelong Wool Combing is used as a case study
Title from title screen
Executive producer, Neil Barrett
Narration: Terrie Waddell
DVD format
Keywords: Geelong Wool Combing; Foreign trade regulation -- Australia; International economic integration